Unveiling the nexus of organizational intelligence, resilience capacity and financial performance - Keskin, Halit; Tatoglu, Ekrem; Akgun, Ali E.; Balak, Dilek (EMERALD GROUP PUBLISHING LTD, 2026)
Purpose-This study synthesizes resource-based and knowledge-based theories with organizational learning principles to investigate the intricate relationships between organizational intelligence (OI), organizational resilience capacity (ORC) and financial performance (FP) within the technology-driven dynamics of modern organizations. By addressing the empirical gap, the research reveals the mediating role of ORC and explores the moderating impact of environmental turbulence. Design/methodology/approach-Drawing on a sample of 318 manufacturing companies in Turkey, this study employs structural equation modeling (SEM) in AMOS to test the formulated hypotheses. FindingsThe study reveals a positive link between OI and ORC, with ORC significantly influencing FP and acting as a full mediator in this relationship. As a dynamic capability, OI notably contributes to financial success. However, when hypothesized to strengthen the OI-ORC link, environmental turbulence unexpectedly weakens this effect, clearly suggesting that heightened turbulence may constrain OI's role in fostering resilience. Research limitations/implications-Limited by its cross-sectional nature, the study suggests the need for longitudinal research for deeper insights. Further exploration is warranted for industry-specific applications and understanding leadership's role in fostering OI and ORC. Practical implications-Organizations are advised to prioritize the development of OI to enhance ORC. Strategies leveraging OI for ORC can improve decision-making, adaptability and overall financial outcomes. Originality/value-Bridging gaps in the literature, the study presents a nuanced understanding of OI's role in fostering ORC and improving FP, presenting implications for organizational strategies in the dynamic landscape shaped by technology. Offering practical insights, it underscores OI as a strategic capability with implications for ORC in turbulent environments.
Keywords: Organizational intelligence; Organizational resilience capacity; Financial performance; Environmental turbulence; Turkey; DYNAMIC CAPABILITIES; KNOWLEDGE MANAGEMENT; FIRM; INNOVATION; FRAMEWORK; BUSINESS; ANTECEDENTS; EMOTIONS; OUTCOMES; IMPACT; Business & Economics